Advanced digital fireball observatories: Enabling the expansion of the desert fireball network - Howie, R.; Paxman, J.; Bland, Phil; Towner, Martin; Cupák, M.; Sansom, E. (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. The Desert Fireball Network (DFN) is an Australian Research Council project designed to track fireballs over approximately one third of Australia. Meteorites with a known orbit, detected and recovered through fireball networks such as the DFN, provide information about the formation and history of the Solar System. The requirements and design of an Advanced Digital Fireball Observatory (ADFO) are presented alongside the design challenges and results of field testing. The deployment of over 60 ADFOs will allow the construction of a flexible continental scale planetary science installation producing high quality all-sky data for meteorite recovery and other uses.